The Role Of Symbols In Modern Literature And Novels (Journal of Pedagogical Inventions and Practices, 2024)
Symbolism describes the use of concrete images to convey abstract ideas. Because this literary device is widely open to interpretation, and because many readers form different relationships to concrete objects, this is one of the more slippery elements of literature to both understand and convey to an audience. Nonetheless, understanding symbolism, and knowing what is a symbol, are crucial to writing good poetry and prose.